Jute Geotextiles and their Applications in Civil Engineering - Sanyal, Tapobrata (Developments in Geotechnical Engineering,, 2017)
This book presents a first-of-its-kind exposition on the emerging technology of jute fibre geotextiles. The book covers the characteristics of jute fibre and jute yarns, types and functions of jute geotextiles, and the mechanism of control of surficial soil with jute geotextiles. The content also includes applications such as the mechanisms of functioning of jute geotextiles in strengthening road sub-grade and controlling river bank erosion, stabilization of earthen embankments, management of settlement of railway tracks, and consolidation of soft soil by use of pre-fabricated vertical jute drains (PVJD). Geotextile standards, properties and test methods, variants of jute geotextiles, economical and environmental advantages in different applications are covered along with a few case studies. A chapter on soil basics is included to enable clearer understanding of soil mechanisms. The book can be used as a reference work or as primary or supporting text for graduate and professional coursework. It will also prove useful to researchers and practicing engineers looking for a comprehensive treatise on jute geotextiles.